Establishment rate and lateral spread of Festuca arundinacea cultivars - St. John, Rodney; Fry, Jack; Bremer, Dale J.; Keeley, Steve (My University, 2009)
Tall fescue (Festuca arundinacea Shreb.) is usually classified as a bunch grass, but produces short rhizomes. Newer tall fescue cultivars have been developed that reportedly produce longer and more numerous rhizomes. This study was conducted to evaluate the establishment rate and lateral spread of ‘Grande II’ and ‘Regiment II’, cultivars with greater rhizome forming capability according to breeders; Water Saver RTF tall fescue blend (RTF blend), which contains the rhizomatous tall fescue ‘Labarinth’; ‘Barlexus’ tall fescue, a non-rhizomatous turf-type cultivar; ‘Kentucky-31’ tall fescue, a non-rhizomatous cultivar originally developed for forage; and SR2284 Kentucky bluegrass (Poa pratensis L.). By six weeks after seeding at Manhattan, KS, USA, Kentucky-31 tall fescue plots had the greatest coverage (80%) and Kentucky bluegrass had the least (60%). Ten months after seeding, plugs were removed from plots and transplanted into bare soil in Manhattan and Olathe, KS. Twenty-one months after transplanting, Kentucky bluegrass plugs had grown to a diameter over twice the size of tall fescue cultivars at Olathe and three times the diameter in Manhattan. Voids were created by cutting a 30.5-cm wide by 10.2-cm deep section sod from the center of each plot, filled with the same field soil, and monitored for encroachment from plants on the perimeter of the void. Void diameters 21 months after creation were 1.0 cm for Kentucky bluegrass and >18 cm for all tall fescue cultivars and the blend, none of which differed in void size. Use of rhizomatous tall fescue cultivars, or a blend containing one such cultivar, did not increase establishment rate or lateral spread relative to tall fescue cultivars not marketed as rhizomatous cultivars.
Keywords: Rhizomes; Rhizomatous tall fescue